2014
DOI: 10.1002/chin.201415268
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Modulating Glycosylation with Exogenous Nucleophiles: An Overview

Abstract: Review: 81 refs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…177,178 The NMR detection and characterization of intermediates in glycosylation reactions was reviewed in 2015, 147 and the use of additives in general was reviewed in 2014. 179 The additive tetraethylammonium bromide was employed by Lemieux and co-workers in their halide-ion-catalyzed approach to axial glycosides from glycosyl bromides. In this seminal work, in what amounts to a demonstration of the Curtin−Hammett principle, the added bromide was considered to displace bromide from the initial axial donor to populate the less stable but more reactive equatorial bromide, which itself was subsequently displaced by the alcohol (Scheme 29).…”
Section: Generation and Characterization Ofmentioning
confidence: 99%
“…177,178 The NMR detection and characterization of intermediates in glycosylation reactions was reviewed in 2015, 147 and the use of additives in general was reviewed in 2014. 179 The additive tetraethylammonium bromide was employed by Lemieux and co-workers in their halide-ion-catalyzed approach to axial glycosides from glycosyl bromides. In this seminal work, in what amounts to a demonstration of the Curtin−Hammett principle, the added bromide was considered to displace bromide from the initial axial donor to populate the less stable but more reactive equatorial bromide, which itself was subsequently displaced by the alcohol (Scheme 29).…”
Section: Generation and Characterization Ofmentioning
confidence: 99%
“…The α-triflate intermediate 2 was then generated in situ as the most plausible intermediate with the departure of the TolSI 5-I byproduct. 46,51,52 Both glycosyl triflate 2 and oxocarbenium ion 26 determined the glycosidic bond formation with acceptor [ROH, (27)] to produce glycoside 30 through the nucleophilic substitution. 18,63−67 In our present research, we also observed the regenerated donor 7 in the reaction mixture.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The central obstacle is that glycosyl triflate 2, which serves as the main intermediate in TfOH-mediated thioglycoside reactions, is highly unstable to analysis. 46,51,52 required for anomeric leaving group activation, 25,53−55 induce the formation of side products 7 and 8 and lower the yield of desired 4. Therefore, the lack of precise mechanistic study leads to indeterminacy, as the reaction yields are drastically fluctuant, even under slight changes of the protecting group, promoter, or temperature.…”
Section: ■ Introductionmentioning
confidence: 99%